2022
DOI: 10.15376/biores.17.2.3042-3056
|View full text |Cite
|
Sign up to set email alerts
|

Copper oxide nanoparticles as fungistat to inhibit mycotoxins and hydrolytic enzyme production by Fusarium incarnatum isolated from garlic biomass

Abstract: Garlic (Allium sativum L.) being infected by mycotoxigenic fungi is one of the primary factors limiting its nutritional and medical value. Therefore, there is an urgent need to repress mycotoxigenic fungi utilizing safer treatments, possibly involving nanoparticles. Fusarium incarnatum was isolated from garlic (A. sativum L.) that showed fungal contamination and their identification was confirmed using amplified and sequenced internal transcribed spacer nuclear ribosomal DNA regions, which confirmed the isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…1, 27.2, 63.8, 55.9, and 44.3%, respectively. In a study where green silver NPs were synthesized from alcoholic extracts of plants, it was stated that these NPs were effective in removing or preventing the production of mycotoxins, especially AFLB1 (Jawad et al 2022b). Al-Rajhi et al (2022) observed that the production of F. incarnatum mycotoxins, such as beauvericins, fusarins, moniliformin, and enniatins, was reduced by as much as 62.8%, 45.4%, 58.1%, and 55.0%, respectively, at a concentration of 400 ppm of copper oxide NPs. Research on milk magnifies the role of aflatoxin M1 in threatening consumers' health and increases interest in the hygienic quality of milk produced.…”
Section: The Aflatoxin-added Solutions Treated With Btfeonp Gtfeonp G...mentioning
confidence: 98%
“…1, 27.2, 63.8, 55.9, and 44.3%, respectively. In a study where green silver NPs were synthesized from alcoholic extracts of plants, it was stated that these NPs were effective in removing or preventing the production of mycotoxins, especially AFLB1 (Jawad et al 2022b). Al-Rajhi et al (2022) observed that the production of F. incarnatum mycotoxins, such as beauvericins, fusarins, moniliformin, and enniatins, was reduced by as much as 62.8%, 45.4%, 58.1%, and 55.0%, respectively, at a concentration of 400 ppm of copper oxide NPs. Research on milk magnifies the role of aflatoxin M1 in threatening consumers' health and increases interest in the hygienic quality of milk produced.…”
Section: The Aflatoxin-added Solutions Treated With Btfeonp Gtfeonp G...mentioning
confidence: 98%
“…ZnO-NPs may maintain the membrane of red blood cells by stopping the expulsion of enzymes that are act lytic agent. Moreover, recent investigation demonstrated that ZnO-NPs possess anti-inflammatory and antioxidant activities (Nagajyothi et al 2015;Al-Rajhi et al 2022a, b).…”
Section: Anti-inflammatory Activity Of Zno-npsmentioning
confidence: 99%
“…One of the main causes of toxin pollution in food and feed is fungi that grow on food. Mycotoxins are fungal secondary metabolites that are produced on a variety of grains, seeds, and food products by several common microscopic toxigenic strains of Penicillium, Aspergillus, and Fusarium (Abdelghany 2006;El-Taher et al 2012;Al-Rajhi et al 2022a;Gedikli et al 2024). Aflatoxins, which include a range of derivatives, are a class of secondary metabolites generated by a polyketone pathway by different fungi, including Aspergillus flavus and A. parasiticus (Abdelghany 2014;Abdelghany et al 2020).…”
Section: Introductionmentioning
confidence: 99%